2019
DOI: 10.1002/ece3.5140
|View full text |Cite
|
Sign up to set email alerts
|

Sympatry and interference of divergent Microbotryum pathogen species

Abstract: The impact of infectious diseases in natural ecosystems is strongly influenced by the degree of pathogen specialization and by the local assemblies of potential host species. This study investigated anther‐smut disease, caused by fungi in the genus Microbotryum , among natural populations of plants in the Caryophyllaceae. A broad geographic survey focused on sites of the disease on multiple host species in sympatry. Analysis of molecular identities for the pathogens revealed that sympatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…The anther-smut fungus lineage of Microbotryum parasitizing the North American native Silene virginica and S. caroliniana constitutes an interesting case of incipient divergence and host specialization. No differentiation was found between the anther-smut fungal populations of these two plant species based on a few molecular markers (Antonovics et al 1996;Freeman et al 2002;Antonovics et al 2003;Hood et al 2019) but their largely distinct pollinator guilds (Fenster and Dudash 2001;Reynolds and Fenster 2008;Reynolds et al 2009) may have promoted reproductive isolation in these pollinator-borne anther-smut fungi. Microbotryum fungi from S. caroliniana are known to carry mating-type chromosomes with large NRRs that have extended in several successive steps, generating a series of successive "evolutionary strata" with varying ages of divergence (Branco et al 2018).…”
Section: Articlementioning
confidence: 89%
“…The anther-smut fungus lineage of Microbotryum parasitizing the North American native Silene virginica and S. caroliniana constitutes an interesting case of incipient divergence and host specialization. No differentiation was found between the anther-smut fungal populations of these two plant species based on a few molecular markers (Antonovics et al 1996;Freeman et al 2002;Antonovics et al 2003;Hood et al 2019) but their largely distinct pollinator guilds (Fenster and Dudash 2001;Reynolds and Fenster 2008;Reynolds et al 2009) may have promoted reproductive isolation in these pollinator-borne anther-smut fungi. Microbotryum fungi from S. caroliniana are known to carry mating-type chromosomes with large NRRs that have extended in several successive steps, generating a series of successive "evolutionary strata" with varying ages of divergence (Branco et al 2018).…”
Section: Articlementioning
confidence: 89%
“…Cross‐species disease transmissions (i.e., spill‐overs of fungal strains) were more frequent on S. nutans than on S. italica , which may be due to unequal sample sizes between the two Silene species or to biological differences. Some Caryophyllaceae plants indeed seem more susceptible to cross‐species transmissions (Antonovics et al, 2002; Hood et al, 2019; de Vienne, Hood, et al, 2009). Putative spill‐overs may actually correspond to other Microbotryum species, which were too rare to be identified in our population analyses using microsatellite markers, as revealed with the whole genome sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…Although host shifts can and do occur between closely related species (Antonovics et al 2002;Refrégier et al 2008;Tyson et al 2018), there has been little evidence to suggest a true generalist species in Silene that is actively maintained on two or more hosts. Indeed, patterns of host-specificity among Silene-infecting Microbotryum are present even in communities with sympatric host species (Van Putten et al 2005;Gladieux et al 2010;Hood et al 2019) and overlapping floral phenologies (Tang et al 2019). One possible explanation for the contrast in host breadth between Microbotryum on Silene and those pathogen lineages on Dianthus is that the Dianthus species studied here were part of very recent radiation that occurred during the early Pleistocene (Valente et al 2010).…”
Section: Variation In Pathogen Host Rangementioning
confidence: 99%
“…Microbotryum species infecting hosts in the genus Silene are highly specialized; each pathogen species is generally found on just a single host species (Le Gac et al 2007). Moreover, this specificity is generally maintained even in sympatry with other closely related host species (Hood et al 2019;Tang et al 2019), although occasional host shifts have been identified (Antonovics et al 2002;Refrégier et al 2008;Tyson et al 2018;Hood et al 2019).…”
mentioning
confidence: 99%